Urban China on Screen: The Sixth Generation and the Postsocialist Cinematic City. Issue 8 (2nd August 2013) - Berra, John
Abstract: This article will consider the relationship between the city and the cinema with regard to the films of China's 'Sixth Generation', a group of filmmakers who mostly graduated from the Beijing Film Academy in the late 1980s and proceeded to make films on the subject of their nation's urban fabric. These are films which utilise city narrative to comment on social–economic change, but largely observe such conditions, rather than to take apolitical stance. To explore the urban representation of the Sixth Generation, this article will provide analysis of three works that depict life in top‐tier or second‐tier mainland China cities: Biandan, guniang / So Close to Paradise (1999), Suzhou he / Suzhou River (2000) and Xiari nuanyangyang / I Love Beijing (2001). The manner in which urban space is represented will be considered, alongside the social positioning of the characters, in order to address arguments made by scholars that these films focus on the plight of the individual rather than considering the wider implications of urban planning.